Experiences od open and closed list local taxes in Hungary with special regard to the effects of the COVID19 pandemic - Bordás, Péter (Review of European and Comparative Law, 2022)
Local taxes account for a significant share of the revenue of Hungarian local governments. In the system developed after the transition to democracy in 1990, local governments were granted the right to set a tax on a closed list, which was supplemented in 2015 by a right to set a tax on an open list. In the case of traditional local taxes, the tax capacity of local government differs greatly, that generates a significant issue in the self-government system. In addition, we can see differences within local taxes, as the role of the business tax is much stronger than other taxes. Dealing with the different resource-generating capabilities that are essential to provide public tasks of the same quality is a systemic regulatory problem. With the introduction of the settlement tax in 2015, Hungarian self-government expected to be able to increase their own revenues and thus their financial independence. But it soon became apparent that in practice there were several regulatory obstacles to achieving this, so the hopes diminished. By now, it has also become clear that the settlement tax did not introduce a significant change in this area, even more, it has damaged the previous revenue structure. The measures adopted during the pandemic in the past year and a half required new regulatory solutions, that also affected the system of local taxes.